Cloud VR Technology and Application. - Huang, Yin.; Lai, Jianfei; Xiong, Huaping; Li, Dawei; Huang, Kun.; Xu, Mu.; Xu, Lingling; Qian, Shengjun (Milton : Taylor & Francis Group, 2020)
Based on the technical accumulation and practice of Huawei iLab in the Cloud VR field, this book systematically describes the advantages of Cloud VR technologies; technical requirements on clouds, networks, and terminals as well as solution implementation; Cloud VR experience evaluation baselines and methods; and current business practices. Cloud VR introduces cloud computing and cloud rendering to VR services. With fast and stable networks, cloud-based display output and audio output are coded, compressed, and transmitted to user terminals, implementing cloud-based VR service content and content rendering. Cloud VR has stringent requirements on bandwidth and latency, making it a proficient application for 5G and gigabit home broadband networks in the era of "dual G". As the first advocate of Cloud VR, Huawei iLab developed the first prototype of the Cloud VR technical solution, initiated the industry's first Cloud VR industry cooperation plan - VR OpenLab with partners - and incubated the world's first Cloud VR commercial project with China Mobile Fujian. Cloud VR: Technology and Application is the first official publication of Huawei iLab's research and practice achievements. It systematically and thoroughly introduces the Cloud VR concept, solution architecture, key technologies, and business practices and is of great value in academic and social applications. This book is easy to understand, practical, and suitable for VR vendors, VR technology enthusiasts, carriers, network vendors, cloud service providers, universities, and other enterprisesand scientific research institutes.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Virtual reality -- Computer programs; Cloud computing; COMPUTERS / Computer Graphics / General; COMPUTERS / Networking / General